The overnight [videorecording (DVD)] - Brice, Patrick; Scott, Adam, 1973-; Schwartzman, Jason, 1980-; Schilling, Taylor, 1984- (Paramount Home Entertainment, 2015)
In an attempt to acclimate to Los Angeles, a young couple spends an increasingly bizarre evening with the parents of their son's new friend.